2000
DOI: 10.1200/jco.2000.18.4.708
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of the Antiangiogenic Agent Thalidomide in Patients With Recurrent High-Grade Gliomas

Abstract: Thalidomide is a generally well-tolerated drug that may have antitumor activity in a minority of patients with recurrent high-grade gliomas. Future studies will better define the usefulness of thalidomide in newly diagnosed patients with malignant gliomas and in combination with radiotherapy and chemotherapy. Additionally, studies will be needed to confirm the potential utility of changes in serum bFGF as a marker of antiangiogenic activity and/or glioma growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
174
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 386 publications
(181 citation statements)
references
References 28 publications
4
174
0
3
Order By: Relevance
“…Other mediators of angiogenesis (including serum VCAM-1, vWF, and urokinase plasminogen activator soluble receptor) hypothesised to be indirect targets of razoxane were significantly higher in progressive disease patients than in stable disease patients before and after one cycle of treatment (Braybrooke et al, 2000). In a Phase II study of the antiangiogenic agent thalidomide, 16 of 36 patients with recurrent, high-grade gliomas that had radiographic and clinically stable disease had either stable or decreased serum bFGF levels (Fine et al, 2000). Interestingly, serum bFGF levels significantly correlated to survival; patients whose serum bFGF significantly decreased (compared to baseline) survived approximately twice as long (43 weeks) than in those patients whose levels increased beyond the third week of therapy.…”
Section: Serum Plasma and Urine Factorsmentioning
confidence: 99%
“…Other mediators of angiogenesis (including serum VCAM-1, vWF, and urokinase plasminogen activator soluble receptor) hypothesised to be indirect targets of razoxane were significantly higher in progressive disease patients than in stable disease patients before and after one cycle of treatment (Braybrooke et al, 2000). In a Phase II study of the antiangiogenic agent thalidomide, 16 of 36 patients with recurrent, high-grade gliomas that had radiographic and clinically stable disease had either stable or decreased serum bFGF levels (Fine et al, 2000). Interestingly, serum bFGF levels significantly correlated to survival; patients whose serum bFGF significantly decreased (compared to baseline) survived approximately twice as long (43 weeks) than in those patients whose levels increased beyond the third week of therapy.…”
Section: Serum Plasma and Urine Factorsmentioning
confidence: 99%
“…These include rheumatoid arthritis (Schuler and Ehninger, 1995), the inflammatory and wasting effects of chronic tuberculosis (Klausner et al, 1996), Behcet's disease (Hamuryudan et al, 1998), Crohn's disease (Wettstein and Meagher, 1997;Ehrenpreis et al, 1999;Vasiliauskas et al, 1999) aphthous ulcers (Youle et al, 1989;Alexander and Wilcox, 1997;Jacobson et al, 1997), cachexia (wasting) associated with HIV infection (Sharpstone et al, 1995;Reyes-Teran et al, 1996) and AIDS-related Kaposi's sarcoma (Fife et al, 1998). There is also a wide body of evidence from large-scale clinical trials showing the effectiveness of thalidomide as a treatment for refractory or relapsed multiple myeloma (MM) (Singhal et al, 1999;Hideshima et al, 2000;Juliusson et al, 2000;Kneller et al, 2000;Zomas et al, 2000), and this extends to the treatment of a number of other tumours (Eisen et al, 2000;Fine et al, 2000;Gutheil and Finucane, 2000;Patt et al, 2000;Tseng et al, 2001;Eisen, 2002).…”
mentioning
confidence: 99%
“…In a basic fibroblast growth factor (bFGF)-induced angiogenesis assay performed in rabbit cornea, it was shown that thalidomide significantly decreased the formation of new vessels 7 and inhibited vascular endothelial growth factor (VEGF)-induced angiogenesis. 8 Several clinical studies indicate that thalidomide may possess antineoplastic properties in myeloma, 9 melanoma, 10 hormonerefractory prostate carcinoma, 11 high-grade glioma, and Kaposi sarcoma. 12 Several considerations support the potential use of thalidomide in patients with HCC.…”
mentioning
confidence: 99%